1988
DOI: 10.1073/pnas.85.7.2284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chondroitin sulfate E proteoglycans and heparin proteoglycans in the secretory granules of human lung mast cells.

Abstract: The predominant subclasses of mast cells in both the rat and the mouse can be distinguished from one another by their preferential synthesis of 35S-labeled proteoglycans that contain either heparin or oversulfated chondroitin sulfate glycosaminoglycans. Mthough [35SIheparin proteoglycans have been isolated from human lung mast cells of 40-70% purity and from a skin biopsy specimen of a patient with urticaria pigmentosa, no highly sulfated chondroitin sulfate proteoglycan has been isolated from any enriched or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Our laboratory has also reported the many biological activities of the chemically fully sulfated poly-and oligosaccharides (Chaidedgumjorn et al, 2002;Suzuki et al, 2001;Toida et al, 1999Toida et al, , 2000. Chondroitin sulfate has been found in many tissues (Suzuki et al, 1968) and cells (Ohhashi et al, 1984;Petersen et al, 1999;Stevens et al, 1988), and has been reported to interact with various biologically important molecules and regulate their functions. We have demonstrated the importance of the content, position, and number of O-sulfo groups in CS for immunological activity of the OVA-stimulated murine splenocytes in vitro (Akiyama et al, 2004;Sakai et al, 2002a).…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 88%
“…Our laboratory has also reported the many biological activities of the chemically fully sulfated poly-and oligosaccharides (Chaidedgumjorn et al, 2002;Suzuki et al, 2001;Toida et al, 1999Toida et al, , 2000. Chondroitin sulfate has been found in many tissues (Suzuki et al, 1968) and cells (Ohhashi et al, 1984;Petersen et al, 1999;Stevens et al, 1988), and has been reported to interact with various biologically important molecules and regulate their functions. We have demonstrated the importance of the content, position, and number of O-sulfo groups in CS for immunological activity of the OVA-stimulated murine splenocytes in vitro (Akiyama et al, 2004;Sakai et al, 2002a).…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 88%
“…Heparin within mast cells is associated with serglycin, which is present in secretion vesicles of many cell types and is often produced as CS proteoglycan (Stevens et al, 1988;Stevens et al, 2000). In serglycin-null mice (sg −/− ), which are otherwise normal, mast cell proteases are missorted and have reduced activity (Åbrink et al, 2004).…”
Section: Gags and Mmpsmentioning
confidence: 99%
“…Remarkably, ChS has been detected in many tissues and host cells (65) , and it has been reported to biologically interact with important molecules and to regulate their functions. It was reported that the Th1-promoting and Th2-inhibitory activities of ChS were associated with its binding to such adhesion molecules as L-and P-selectins, clustter of differentiation 4 (CD4) molecules, and chemokines (66) . The immune-stimulatory activity of ChS may be due to its binding to L-selectins expressed on the T cell surface (67) .…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 99%